An experimental analysis on the influence of flow direction changes on the transitions in gas-liquid, slug-to-stratified downward flows. (October 2019) - Alves, Rafael F.; Schneider, Fábio A.; Barbuto, Fausto A.; Santos, Paulo H.D.; Morales, Rigoberto E.M.
Highlights: The article presents an experimental study on two-phase gas-liquid slug flows in pipes with a slight direction change. High-speed cameras and four resistive sensor-equipped metering stations were used to collect data. A noteworthy difference between some experimental points that actually showed stratified flow and the flow regimes predicted by a traditional flow pattern map was observed. Slug-to-stratified transitional flow in the downward section was observed under some test conditions. Interpretation of the results were based upon sound statistical analyses. Abstract: An experimental study on two-phase gas-liquid slug flows in pipes with a slight direction change is presented. A lab rig composed of a horizontal tubular section followed by a downward inclined pipe of the same diameter but at different inclinations was assembled. Resistive sensors were installed at four different pipe locations (herein referred to as "test sections"), so as to measure characteristic flow parameters. Two high-speed cameras were used to visualize and identify flow phenomena. Experiments under slug flow conditions in the horizontal section at different gas and liquid flow rates were carried out. In some test conditions the slug-to-stratified transition in the downward section was observed. The mechanism causing flow stratification was associated to the liquid film acceleration during its transit through the elbow, as the film flows at velocities occasionally higher than those of the liquid slug. Thus, the liquid slug sheds liquid to the film ahead, making the elongated bubble to penetrate into the liquid slug region, leading to the onset of a stratified flow. A noteworthy difference between the number of experimental points that actually showed stratified flow and the flow patterns predicted for the same points by a downward flow pattern map was observed. Therefore, the model presented by Taitel et al. (Slug flow modeling for downward inclined pipe flow: theoretical considerations. International Journal of Multiphase Flow, Vol. 26, No. 5, pp. 833–844, 2000) was selected for predicting transitions in this specific flow condition – that is, from horizontal to downward flow with a direction change. The results obtained with this kind of modelling showed to be consistent with the experiments.